A case of idiopathic ventricular tachycardia in a 14-year-old obese patient due to golden berry fruit extract pills for weight loss - Hakkı Şimşek; Adnan Doğan; Musa Şahin; Hasan Ali Gümrükçüoğlu (KARE Publishing, 2013)
Several studies have determined an association between obesity and increased risk of cardiac arrhythmia. Currently, due to the increased frequency of obesity, food-, plant-, and drug-based therapies for weight loss have gained great attention. A 14-year-old female patient presented with complaints of palpitation of one-hour onset. Blood pressure was 110/70 mmHg and peripheral pulses were present. She had been using golden berry extract pill three times a day for 10 days. The electrocardiogram showed nonsustained monomorphic ventricular tachycardia (VT). Echocardiographic examination and cardiac magnetic resonance imaging (MRI) were normal. She returned to sinus rhythm following amiodarone infusion. She refused the electrophysiologic study, which plays a vital role in the diagnosis and establishment of the appropriate therapy. Although there was no decrease in body mass index (BMI) of the patient during the two-year follow-up, she had no complaint or evidence of VT on intermittent rhythm Holter studies. This case suggests the primary role of golden berry extract use in the development of VT, rather than obesity.